Successful treatment of high-risk myelodysplastic syndrome with decitabine-based chemotherapy followed by haploidentical lymphocyte infusion: A case report and literature review. Issue 16 (April 2018) - Ma, Yuanyuan; Shen, Jianliang; Wang, Li-Xin
Abstract: Rationale: The current therapy for elderly patients with high-risk myelodysplastic syndromes (MDSs) remains unsatisfactory. Decitabine, which has been approved to treat MDS, cannot eliminate malignant clones of MDS. Patient concerns: A 68-year-old woman presented with multiple divergent bleeding points in the subcutaneous tissue of the limb. Two years earlier, she had been diagnosed with invasive ductal carcinoma of the left breast and had undergone left modified radical mastectomy and local radiation therapy. Diagnoses: The patient was diagnosed with MDS refractory anemia with excess of blast II and was classified as very high risk according to the revised international prognostic scoring system. Interventions: The chemotherapy regimen consisted of decitabine (20 mg/m 2 intravenously on days 1–5), cytarabine (10 mg/m 2 every 12 hours subcutaneously on days 1–5), aclarubicin hydrochloride (20 mg intravenously on days 1, 3, and 5), and recombinant human granulocyte colony-stimulating factor (250 μg/d subcutaneously from day 0 to day 5). Peripheral mononuclear cells from her son were infused at 36 hours after the end of each chemotherapy cycle. The patient received a total of 4 cycles of the therapy. Outcomes: The patient achieved complete remission after the first cycle of the treatment. There was no clinical evidence of MDS relapse as of 4 years after the completion of the treatment. Lessons: The results suggested that decitabine-based chemotherapy and haploidentical lymphocyte infusion may be act synergistically. Combination therapy is a suitable, safe, and effective treatment regimen for elderly patients with high-risk MDS.